2012
DOI: 10.1007/s00441-012-1510-9
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory effects of resistin on human smooth muscle cells: up-regulation of fractalkine and its receptor, CX3CR1 expression by TLR4 and Gi-protein pathways

Abstract: In the atherosclerotic plaque, smooth muscle cells (SMC) acquire an inflammatory phenotype. Resistin and fractalkine (CX3CL1) are found in human atheroma and not in normal arteries. CX3CL1 and CX3CR1 are predominately associated with SMC. We have questioned whether resistin has a role in the expression of CX3CL1 and CX3CR1 in SMC thus contributing to the pro-inflammatory status of these cells. Cultured human aortic SMC were stimulated with 100 ng/ml resistin for 4, 6, 12, and 24 h, and then CX3CL1 and CX3CR1 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 42 publications
3
40
0
Order By: Relevance
“…This pathway plays an important role in inflammatory activation, proliferation and migration and restenosis of vascular smooth muscle cells. Restenosis requires the acquisition of an inflammatory phenotype of smooth muscle cells, and TLR4/MyD88/NF-κB is a critical promoting factor for the phenotypic acquisition of the cells [40][41][42]. Therefore, activation of the TLR4/MyD88/NF-κB pathway is closely associated with restenosis, and the LPS-induced HCASMC inflammatory activation model can serve as a reliable cell model for research on the restenosis mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…This pathway plays an important role in inflammatory activation, proliferation and migration and restenosis of vascular smooth muscle cells. Restenosis requires the acquisition of an inflammatory phenotype of smooth muscle cells, and TLR4/MyD88/NF-κB is a critical promoting factor for the phenotypic acquisition of the cells [40][41][42]. Therefore, activation of the TLR4/MyD88/NF-κB pathway is closely associated with restenosis, and the LPS-induced HCASMC inflammatory activation model can serve as a reliable cell model for research on the restenosis mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Under basal conditions, the concentration and activity of AP-1 are relatively low (30). When cells are stimulated, AP-1 expression increases (30). The results of the current study indicated that geniposide reduces AP-1 protein expression in mouse epilepsy.…”
Section: Discussionmentioning
confidence: 48%
“…AP-1 is a homodimer or heterodimer of c-fos and c-jun. Under basal conditions, the concentration and activity of AP-1 are relatively low (30). When cells are stimulated, AP-1 expression increases (30).…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have reported that resistin may indicate the severity of the disease in patients with neonatal sepsis, in a similar manner to IL-6 and CRP (7,14,23,24). Furthermore, recent studies have demonstrated that resistin may serve a function in inflammation and autoimmunity (5,25). Bokarewa et al reported that the use of recombinant resistin resulted in a marked upregulation in the genes for tumor necrosis factor (TNF)-α and IL-6 (26).…”
Section: Discussionmentioning
confidence: 99%
“…Resistin competes with lipopolysaccharides through binding to Toll-like receptors and may function as a proinflammatory cytokine in human monocytes. In addition, resistin is a member of the cysteine-rich secretory protein family, members of which are also known as resistin-like or ʻfound in inflammatory zoneʼ molecules (5). Serum resistin levels have been observed to increase during severe bacterial and viral infections (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%